Penurunan Kandungan Chemical Oxigen Demand (COD) dan Total Suspended Solid (TSS) Limbah Cair Industri Soun Menggunakan Proses Koagulasi-Flokulasi - Darda Ibrahim; Neni Damajanti (UM Purwokerto Press, 2026)
Vermicelli industry is one of the food industries that produces wastewater containing high levels of organic matter and suspended solids, as indicated by elevated Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS) values. These pollutants pose a risk to the environment if not properly treated. One of the methods that can be applied to reduce pollutant levels is the coagulation-flocculation process. This study aims to examine the effects of various coagulation-flocculation process variables on the reduction of COD and TSS in vermicelli industry wastewater and to determine the most influential factors affecting the removal efficiency of both parameters. The treatment process was carried out using the coagulation-flocculation method, with a full factorial design experiment involving four main independent variables at two levels (high and low): coagulant dose (100, 300 mg/L), rapid mixing speed (100, 300 rpm), flocculation speed (10, 30 rpm), and settling time (30, 50 minutes). The analysis results indicated that chitosan dose and settling time were the most influential variables in reducing COD levels, while settling time had the greatest impact on TSS reduction. These findings demonstrate that the effectiveness of the coagulation-flocculation process is highly dependent on proper adjustment of process parameters, making the selection of optimal operating conditions essential for efficient wastewater treatment in the vermicelli industry. Furthermore, this process highlights the potential of chitosan as an environmentally friendly coagulant for treating food industry wastewater.